Self-Compassion and Aggression in College Students - Ferdi W. Djajadisastra (ANIMA Indonesian Psychological Journal, 2017)
The growing number of violence among Indonesian college students demanded further attention. Thus, a study is needed to understand the predictors of aggression among college students. The author proposed that self-compassion was related to aggression. The purpose of this study was to investigate the relationship between self-compassion and aggression in college students. This study involved 300 college students from three different universities in Jakarta and Depok as research participants. Data collection was conducted using self-report measures. It was found that there was a significantly negative relationship between self-compassion and aggression in college students. The result indicates that high self-compassion was related to low aggression in college students.